Anti-Inflammatory Potential of Hexane Extract of Mud Lobster (Thalassina anomala) in Lipopolysaccharide-Stimulated RAW 264.7 Macrophages - Nur Nadiah Zakaria,; Masnindah Malahubban,; Sharida Fakurazi,; Wong Sie Chuong,; Amy Halimah Rajaee, (Tropical Life Sciences Research, 2021)
Mud lobsters are crustaceans from the genus Thalassina which are lesser known and seldom seen, but are nevertheless an important organism to the mangrove ecosystem. In Malaysia and Thailand, mud lobsters are eaten by locals as treatment for asthma. It is traditionally believed that they are effective in reducing the number of asthma attacks and severity of asthma symptoms. However, the therapeutic potential of mud lobster extract remains unclear and has not been fully elucidated or reported in any scientific study. The objectives of this study are to investigate the anti-inflammatory potential of mud lobster, Thalassina anomala extracts (hexane, chloroform and methanol ) in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages, and to identify the potential bioactive compounds involved. An MTT assay was performed to determine the cytotoxicity of the T. anomala extracts on RAW 264.7 macrophages. Nitrite quantification assay and enzyme-linked immunosorbent assay (ELISA) were conducted to investigate the ability of the T. anomala extracts to suppress the secretion and expression of nitric oxide (NO), Prostaglandin E2 (PGE2) and proinflammatory cytokines (TNF-?, IL-6 and IL-1?) in LPS-stimulated macrophages. GC-MS analysis was done to identify putative metabolites. The hexane extract of T. anomala showed anti-inflammatory activity by significantly inhibiting the LPS-induced production of NO, PGE2, interleukin- (IL-) 6, IL-1? and tumour necrosis factor-alpha (TNF-?) in a concentration-dependent manner. Hexane extract treatment with 100 µg/mL has decreased the NO secretion into 37 µM. Meanwhile, hexane extract at concentration of 100 µg/mL able to significantly suppressed PGE2,TNF-?, IL-6 and IL-1? production into 2015 pg/mL, 2406 pg/mL, 460 pg/mL and 9.6 pg/mL respectively. GC-MS analysis of the hexane extract revealed the presence of 19 putative compounds. The identified compounds were reported to have anti-inflammatory, antioxidant and antibacterial activities. These results suggest that the hexane extract of T. anomala potentially has anti-inflammatory properties and concentration dependently suppressed NO, PGE2 and proinflammatory cytokines’ production in LPS-stimulated macrophages. The findings provide a rational basis of the traditional use of mud lobster for inflammation-associated ailments.